PRO KONTRA NASIKH MANSUKH DALAM AL-QUR’AN - Khudori, Muhammad (Mahad Aly Al Fithrah Press, 2018)
One of the methods used to understand the content of the verses which at first glance shows the symptoms of contradiction between one another is the theory of naskh (nasikh-mansukh). Al-Naskh in the terms of the usul’stheologians is the annulment of the enactment of shar‘i law with the postulate that came later which shows the cancellation of the law's enforcement explicitly or implicitly, with the total or partial cancellation, because of a welfare that wants it. In the theory of completion of postulates that are technically considered contradictory, this theory ranks third after al-jam‘u wa al-tawfiq (comparation) and tarjih (featuring one of the postulates). But in his journey the theory of naskh in al-Qur'an experiencing debate among the theologians. Faction majority argues that naskh occurs in the Qur'an. This group at once confirms that naskh is one option of textually contradictory verses after the theory of jam‘u and tarjih can not solve it. While some theologians led by Abu Muslim al-Asfahani argue that in the Qur'an does not apply the naskh, so practically according to this group, the completion of textually contradictory verses only using the theories of jam‘u and tarjih. According to them, all contradictory verses can be compromised without having to abort other verses. The majority of theologians argue that the naskh is reasonably not impossible, because it is purely preogrative right of Allah Swt. While the Abu Muslim’sfaction argues that the Naskh is a cancellation of the law, so that if among the laws that exist in the Qur'an being naskh, means there are verses that are abrogated Qur'an. This is certainly contrary to the word of Allah Almighty.